Upaya Mengurangi Biaya Persediaan Bahan Baku pada Strategi Hybriddi PT. T - Sarah Citrawati; Chaznin R. Muhammad; Reni Amaranti (Jurnal Riset Teknik Industri, 2023)
Abstract. PT. T is a company in Bandung engaged in the food sector. PT. T produces bread, pastries, sauces, tarts, cakes, and processed meats. PT. T sells production in stores (MTS strategy) and accepts consumer orders (MTO strategy). PT. T orders the same number of raw materials for each order—meanwhile, the raw materials used by PT. T is food raw materials that have characteristics with a certain shelf life. Based on the problems in PT. T, a procedure is proposed to determine the number of raw materials that must be prepared to reduce the Total Inventory Cost by considering the expiration date of raw materials in companies implementing a hybrid strategy. The procedure is to determine the Decoupling Point, calculate forecasting, prepare a Master Production Schedule (MPS), and calculate Material Requirement Planning (MRP). After calculating the proposed procedure, the Total Inventory Cost for the EOQ method is IDR. 224.225.833, and the Total Inventory Cost on the EOQ method, which considers expiration is IDR. 213.412.375. This shows that by using the proposed EOQ procedure and considering the expiration date, the company can reduce the Total Inventory Cost by IDR. 95.724.293. Abstrak. PT T merupakan perusahaan di Bandung yang bergerak di bidang makanan. PT T memproduksi roti, kue kering, soes, tart, bolu, dan daging olahan. PT T menjual hasil produksi di toko (strategi MTS) dan menerima pesanan dari konsumen (strategi MTO). PT T memesan bahan baku dalam jumlah yang sama untuk setiap pemesanan. Sedangkan bahan baku yang digunakan oleh PT T adalah bahan baku makanan yang memiliki karakteristik dengan umur simpan tertentu.Berdasarkan permasalahan di PT T, diusulkan prosedur untuk menentukan jumlah bahan baku yang harus disiapkan untuk menekan Total Inventory Cost dengan memperhatikan tanggal kadaluwarsa bahan baku di perusahaan yang menerapkan strategi hybrid. Prosedurnya adalah menentukan Decoupling Point, menghitung forecasting, menyusun Master Production Schedule (MPS), dan menghitung Material Requirement Planning (MRP). , dan Total Inventory Cost pada metode EOQ yang mempertimbangkan kadaluarsa adalah Rp 213.412.375 Hal ini menunjukkan bahwa dengan menggunakan prosedur EOQ yang diusulkan dan mempertimbangkan tanggal kadaluwarsa, perusahaan dapat menurunkan Total Inventory Cost sebesar Rp. 95.724.293.